Building a Sustainable Global Surgery Nonprofit Organization at an Academic Institution - Margaret M. Frisella (Ubiquity Press, 2016)
Background Surgical Outreach for the Americas is a 501(c)3 nonprofit organization providing surgical care to those in need in developing countries of the Western Hemisphere. Every year since its inception in 2008, teams of surgeons, nurses, and allied health professionals have traveled to areas of need and performed primarily hernia repair surgeries for those without access to affordable health care. Methods Surgical Outreach for the Americas (SOfA) began as a general concept based on World Health Organization statistics claiming that 11% of the global burden of disease can be resolved via surgery. Armed with this information, a group of compassionate and selfless health care professionals planned the first trip, to the Dominican Republic, in January 2009. Building on what was first just an ambition to help others, we now also train surgeons, surgery residents, and nurses in the countries we serve. Findings To date, SOfA has successfully treated 734 patients, with 899 total surgical procedures performed (693 of these under general anesthesia). These procedures include inguinal inguinal hernia, umbilical hernia, testicular masses, orchiectomies, and various general surgical procedures. Conclusions Through the efforts of a great many talented individuals and robust fundraising efforts, the SOfA message continues to gain momentum. SOfA not only considers the health and well-being of the disadvantaged through capacity-building efforts but strives to educate and improve the skills of health care professionals in the countries we visit. Our goal is to increase the number of missions each year and begin a 2-fold educational program that (a) provides surgical resident education through participation in mission work and (b) provides local surgeon education in the areas served.